2001
DOI: 10.1055/s-2001-13355
|View full text |Cite
|
Sign up to set email alerts
|

A Carbonyl Ylide Approach to Substituted Furans

Abstract: The diazosulphone 1 undergoes intermolecular reaction with aldehydes to form carbonyl ylides 2. This reactive intermediate can then be trapped, in an inter-or intramolecular reaction, by alkynes or alkenes to yield substituted furans or tetrahydrofurans respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…In contrast, analogous two component reactions involving tandem intermolecular ylide formation/intramolecular cycloaddition has been relatively limited (Scheme 1d). In 2001, Johnson and co‐workers described an interesting example of rhodium‐catalyzed intermolecular ylide for‐mation/intramolecular cycloaddition of diazosulphone and alkynyl/alkenyl aldehydes, affording substituted furans or tetrahydrofurans [6] . Recently, Muthusamy et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, analogous two component reactions involving tandem intermolecular ylide formation/intramolecular cycloaddition has been relatively limited (Scheme 1d). In 2001, Johnson and co‐workers described an interesting example of rhodium‐catalyzed intermolecular ylide for‐mation/intramolecular cycloaddition of diazosulphone and alkynyl/alkenyl aldehydes, affording substituted furans or tetrahydrofurans [6] . Recently, Muthusamy et al.…”
Section: Methodsmentioning
confidence: 99%
“…In 2001, Johnson and co-workers described an interesting example of rhodium-catalyzed intermolecular ylide for-mation/intramolecular cycloaddition of diazosulphone and alkynyl/alkenyl aldehydes, affording substituted furans or tetrahydrofurans. [6] Recently, Muthusamy et al developed a copper-catalyzed tandem reaction of diazoamides and O-propargyl salicylaldehydes for the synthesis of spiro-indolofurobenzopyrans via intermolecular ylide formation/intramolecular cycloaddition process; [7] in comparison, Bakthadoss et al reported a similar rhodium-catalyzed protocol of diazo dicarbonyl compounds and O-allylated salicylaldehydes for the construction of tricyclic chromeno/ quinolino furan frameworks. [8] Despite these considerable advances, there was still not a general method for the two-component intermolecular ylide formation/ intramolecular cycloaddition with broad scope and control over chemo-and diastereoselectivity.…”
mentioning
confidence: 99%
“…It is not surprising, considering the range of possibilities as shown in Scheme 1, that these compounds continue to be important for constructing complex natural product targets. It is worthy to note, that also -diazoorganophosphorus [15,16] anddiazoorganosulfur [17] compound are attractive and versatile synthetic blocks that have been investigated and applied in several synthesis. This review will focus specifically on current strategies, which involve diazo compounds in the construction of important heterocycle rings by inter and intramolecular insertion reactions (Scheme 2).…”
Section: Scope Of Carbenoid Transfer Reactionsmentioning
confidence: 99%
“…Fused furan 20 was formed by intramolecular [3 ϩ 2] cycloaddition of the acetylene group of 19 and an oxonium ylide formed by carbene addition to the aldehyde of 19, followed by elimination of sulfinic acid (Scheme 19). 31 A range of substrates was investigated, including alkenyl aldehydes, which gave tetrahydrofuran products.…”
Section: Five-membered Ringsmentioning
confidence: 99%